Awareness and education of medical students toward artificial intelligence and radiology: A cross-sectional multicenter survey at Kanpur, Uttar Pradesh - Rohan Sachdev; Kriti Garg; Akash Srivastava (Wolters Kluwer Medknow Publications, 2021)
Context: Artificial intelligence (AI) is focused on understanding the essence of human intelligence and developing smart artifacts that can perform the tasks that intelligence is said to entail when performed by humans. Aims: The aim of the study was to understand medical students views, understanding and level of confidence in working on AI and explore if AI influences their career intentions with specific regard to radiology. Settings and Design: 401 medical students of two medical colleges were included. Subjects and Methods: Four and one medical students of two medical colleges were included to complete an anonymous electronic survey consisting of Likert and dichotomous questions. Statistical Analysis Used: Statistical analysis was performed with simple descriptive statistics in frequency and percentages. Results: In this study, 89.11% was the response rate of participants and majority (30.9%) of medical students strongly agreed about the awareness of AI. Nearly 36.3% of the medical students disagreed that they were less likely to consider a career in radiology due to AI. Around 29% of medical students strongly agreed for the scope of integration of AI in medical education of India. Conclusions: Medical students recognize the significance of AI and are eager to get involved. AI medical college curriculum should be broadened and upgraded. Students must be provided with practical use cases and drawbacks of AI so that they may not feel discouraged from pursuing radiology.